Remote sensing and geographic information systems for inflow estimation in reservoir operations - Sarmiento, Czar Jakiri Soriano (2010)
In managing a multipurpose dam, knowledge of water inflow or the amount of water entering the reservoir is essential in planning and scheduling discharges for optimal power production and irrigation supply, and in flood control. Utilization of satellite imagery improves inflow estimates provided by digital spatial data rather than calculations from drawn maps. Satellite imagery yields measurements over an area are obtained instead of extrapolations from point measurements.
Using remote sensing data and GIS, two approaches are developed in this study to estimate inflow: (1) Creation of IMBAC (Inflow Monitoring form Basin Assessment Calculations), a new inflow estimation system using available satellite-derived data and JAVA programming; and (2) Maximizing the use of satellite-derived data for inflow estimation in an existing hydrologic modelling system, the US Army Corps of Engineers' HEC-HMS where three different basin models are used to validate the results- the initial constant model, the SCS curve number model, and the soil moisture accounting model.
The developed approaches to estimate inflow are applied to the Magat watershed; its dam is one of the largest multipurpose dams in Southeast Asia. Its 117-km2 reservoir stores water to irrigate 85, 000 gectares of farmland and its 360-MW hydro-power plant provides electricity for Luzon, the Philippines' largest island. Due to the implementation of the Philippine Electric Power Industry Reform Act (EPIRA) in 2001, management of the reservoir and the dam facilities has to be shared. The dam and the plant intake gates are owned and separated by the national Irrigation Administration. Management of the plant itself is transferred to SN Aboitiz Power Incorporated (SBNAP). Authorization of discharges during extreme weather conditions comes from the country's meteorological agency, the PAGASA. With such a complex nature of the dm's multi stakeholders management involving private and public entities with different discharge motivations, a vital decision support system that concerns inflow estimation is paramount.
Thus study presents the results of the developed methodology to estimate inflow using remote sensing as an alternative to the current water-level approach being used locally. It shows that both the IMBAC and the HEC-HMS approach were successful in showing the behavior of watershed response. The second approach was successful in terms of the immediate potential for operational use.
"April 2010."
Thesis (M.S. Remote Sensing)--University of the Philippines Diliman.
Keywords: Watershed Management -- Philippines